Analysis of an SEIS Epidemic Model with a Changing Delitescence - Jinghai Wang (Abstract and Applied Analysis)
An SEIS epidemic model with a changing delitescence is studied. The disease-free equilibrium and the endemic equilibrium of the model are studied as well. It is shown that the disease-free equilibrium is globally stable under suitable conditions. Moreover, we also show that the unique endemic equilibrium of the system is globally asymptotically stable under certain conditions.